PENGARUH PEREBUTAN WILAYAH KASHMIR TERHADAP HUBUNGAN DIPLOMATIK INDIA-PAKISTAN PERIODE 2011 - 2013 - Rizky, Alfi; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research is a study of diplomacy which discusses about Seize The Effect of Diplomatic Relations on Territory of Kashmir India - Pakistan in 2011 â€“ 2013. Conflict between India and Pakistan in Kashmir issue unresolved until recently seemed to have sunk from the international community. However the presence of kashmir issue has become one of the things that are the focus india - pakistan for many - years. The diplomatic relations between India - Pakistan determined by Kashmir case. In this research, the author uses the Nation â€“ state analysis level which focused on decision making in any situation. This research uses realism perspective in international relations and theory of National Security.Kashmir is an area that lies between India and Pakistan. This area is famous for its natural riches contained therein. The soil is fertile, the rivers that flow throughout the year and their biological minerals make this region a source of conflict India and Pakistan. The conflict began when India and Pakistan officially separated since the announcement of the independence of both sides pidak in 1948. This separation is prolonged impact on the border region, especially in Kashmir, which is fertile.Realism have the assumption that one alternative way conflict resolution is a War. It was then known by the term â€œCivis Pasum Para Bellumâ€ which is means if yo want to make peace them, be prepared for war. Based on the assumption of the theory of realism, the best way conflict resolution between India and Pakistan is a war.Keyword : Kashmir, War, Realism, Diplomatic Relations,Territory.